2021
DOI: 10.3390/life11030184
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Infant Death Syndrome: Beyond Risk Factors

Abstract: Sudden infant death syndrome (SIDS) is defined as “the sudden death of an infant under 1 year of age which remains unexplained after thorough investigation including a complete autopsy, death scene investigation, and detailed clinical and pathological review”. A significant decrease of SIDS deaths occurred in the last decades in most countries after the beginning of national campaigns, mainly as a consequence of the implementation of risk reduction action mostly concentrating on the improvement of sleep condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…6 There is emerging consensus that SUDP represents a heterogeneous grouping of rare and undiagnosed diseases presenting with death and sometimes involve genetic mechanisms. 7,8 Genetic contributions to SUDP are supported by studies of families whose children died from SIDS during the "safe sleep" era, which showed an increased risk for recurrence in subsequent siblings (odds ratio, [OR], 4.2) and within 3 generations (OR, 9.3). 9 The prevailing etiologic model of SUDP postulates that modest extrinsic threats become fatal in infants and children who harbor intrinsic vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…6 There is emerging consensus that SUDP represents a heterogeneous grouping of rare and undiagnosed diseases presenting with death and sometimes involve genetic mechanisms. 7,8 Genetic contributions to SUDP are supported by studies of families whose children died from SIDS during the "safe sleep" era, which showed an increased risk for recurrence in subsequent siblings (odds ratio, [OR], 4.2) and within 3 generations (OR, 9.3). 9 The prevailing etiologic model of SUDP postulates that modest extrinsic threats become fatal in infants and children who harbor intrinsic vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…There is no definitive diagnosis of SIDS, and the underlying cause is not clear [ 8 , 47 ]. SIDS is a diagnosis of exclusion—as such, it is an unexpected death in terms of a previous disease, not explained by a detailed and thorough autopsy or the results of laboratory tests and accompanied by knowledge of all the circumstances from the site of death [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Omics technologies provide a large amount of data, which, when used in a univariate or multivariate manner, could contribute to the detection of the risk profile of the patient who dies from SIDS [ 14 ]. The large amount of data, which is produced with new technologies, benefits from the analysis with machine learning techniques.…”
Section: Introductionmentioning
confidence: 99%